2018
DOI: 10.1097/wnr.0000000000001124
|View full text |Cite
|
Sign up to set email alerts
|

MiR-592 suppresses the development of glioma by regulating Rho-associated protein kinase

Abstract: MicroRNAs are a class of small noncoding RNAs that regulate the translation of target mRNA transcripts. MiR-592 has been considered to play important roles in the initiation and progression of cancer by targeting various molecules in several human cancers, but its role in glioma has not been explored. This study aims to explore the suppressive mechanism of miR-592 in the regulation of glioma development, an effect that is crucial for the further exploration of miR-592 as a novel therapeutic target for glioma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…22 Additionally, ROCK1 was also found to be involved in the regulation of glioma development. 23,24 Thus, we further explored whether miR-206 or ROCK1 were implicated in propofol-mediated regulation on glioma cells.…”
Section: Introductionmentioning
confidence: 99%
“…22 Additionally, ROCK1 was also found to be involved in the regulation of glioma development. 23,24 Thus, we further explored whether miR-206 or ROCK1 were implicated in propofol-mediated regulation on glioma cells.…”
Section: Introductionmentioning
confidence: 99%
“…The biological impact of miR-592 has been reported across several malignancies, including breast, gastric and non-small cell lung cancer ( 26 28 ); however, whether miR-592 takes on the role of an oncogene or tumor suppressor is dependent on the tumor context. For example, miR-592 has been reported to be significantly downregulated in glioma, suppressing the development of glioma by regulating Rho-associated protein kinase ( 29 ). However, He et al ( 27 ) demonstrated that miR-592 is upregulated in gastric cancer (GC), promoting GC cell proliferation, migration and invasion, while inducing endothelial-to-mesenchymal transition via the phosphoinositide 3-kinase/AKT and mitogen-activated protein kinase/extracellular signal-regulated kinase signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-592 is decreased in breast cancer and is associated with malignant clinicopathological characteristics (24). miR-592 expression was also reported to be reduced in glioma (25,26) and hepatocellular carcinoma (27)(28)(29). On the contrary, miR-592 is upregulated in prostate (30) and colorectal (31,32) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…miR-592 exerts an inhibitory role in breast cancer through regulating cell growth and metastasis in vitro, as well as tumor growth in vivo (24). miR-592 was also identified as a tumor-suppressing miRNA in non-small cell lung cancer (23), glioma (25,26), and hepatocellular carcinoma (27)(28)(29), serving dispensable roles in regulating a wide range of biological behaviors. On the contrary, miR-592 was found to play tumor-promoting roles in prostate (30) and colorectal (31,32) cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation